2018
DOI: 10.1038/s41598-018-23455-7
|View full text |Cite
|
Sign up to set email alerts
|

Information about peer choices shapes human risky decision-making

Abstract: Humans frequently make choices that involve risk for health and well-being. At the same time, information about others’ choices is omnipresent due to new forms of social media and information technology. However, while past research has shown that peers can exert a strong influence on such risky choices, understanding how information about risky decisions of others affects one’s own risky decisions is still lacking. We therefore developed a behavioral task to measure how information about peer choices affects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 57 publications
1
10
0
1
Order By: Relevance
“…and the absence of A.a. were also proven to be independent risk factors of RA. This is consistent with already accepted findings regarding the established risk factors of RA [ 46 , 47 ]. The only exception in this context is the absence of A.a. as a risk factor for RA in this multivariate evaluation.…”
Section: Discussionsupporting
confidence: 93%
“…and the absence of A.a. were also proven to be independent risk factors of RA. This is consistent with already accepted findings regarding the established risk factors of RA [ 46 , 47 ]. The only exception in this context is the absence of A.a. as a risk factor for RA in this multivariate evaluation.…”
Section: Discussionsupporting
confidence: 93%
“…Our findings build on previous work showing that knowledge of others’ decisions impacts decisions to take risks. In one study using a monetary risk-taking task (the Balloon Analogue Risk Task, in which individuals pump up a virtual balloon for money and with each pump the risk of it popping increases), individuals took more or less risky choices when presented with the knowledge that others had made high or low risky choices, respectively ( Tomova & Pessoa, 2018 ). In another study which investigated the effects of social norms on simulated risky driving performance, adolescents (16–18 years) made more risky decisions when watched by risk-accepting versus risk-averse age-matched peers ( Simons-Morton et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…The previous meta-analysis showed that the association with peer smoking was greater compared to family members [39]. A laboratory-based behavioral study found that the risky decisions of adolescents was influenced by the choices of their peers [40]. Furthermore, adolescents tended to imitate conventional cigarette smoking behaviors of others that were associated with their social context and shared a common normative belief [41].…”
Section: Jhrmentioning
confidence: 99%